Alignment system for SGII-Up laser facility. (1st March 2018) - Gao, Yanqi; Cui, Yong; Li, Hong; Gong, Lei; Lin, Qiang; Liu, Daizhong; Zhu, Baoqiang; Ma, Weixin; Zhu, Jian; Lin, Zunqi
Highlights: The alignment system of SGII-Up laser facility and its characteristics are reported. The far-field beam pointing alignment accuracy is better than 3 μrad. The alignment error of the near-field beam centering is no larger than 1 mm. The crystal alignment accuracy is better than 4.7 µrad. More than 100 shots are carried out on this system, the maximal energy reached 17 kJ. Abstract: The SGII-Up laser facility in Shanghai is one of the most important high-power laser facilities in China. It is designed to obtain 24 kJ (3ω) of energy with a square pulse of 3 ns using eight laser beams (two bundles). To satisfy the requirements for the safety, efficiency, and quality, an alignment system is developed for this facility. This alignment system can perform automatic alignment of the preamplifier system, main amplifier system, and harmonic conversion system within 30 min before every shot during the routine operation of the facility. In this article, an overview of the alignment system is first presented. Then, its alignment characteristics are discussed, along with the alignment process. Finally, experimental results, including the alignment results and the facility performance, are reported. The results show that the far-field beam pointing alignment accuracy is better than 3 μrad, and the alignment error of the near-field beam centering is no larger than 1 mm. These satisfy the design requirements very well.